2015
DOI: 10.1002/adom.201400545
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area Low‐Cost Tunable Plasmonic Perfect Absorber in the Near Infrared by Colloidal Etching Lithography

Abstract: Optical elements with absorbance close to unity are of crucial importance for diverse applications, ranging from thermal imaging to sensitive trace gas detection. A key factor for the performance of such devices is the need for absorbance with high acceptance angles, which are able to utilize all incident radiation from the forward‐facing half‐space. Here, a tunable, angle‐, and polarization independent large‐area perfect absorber is reported, which is fabricated by a combination of colloidal lithography and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…This offers significantly improved performance compared to Walter et al who presented reflection changes in Pd nanodiscs or Tittl et al who demonstrated perfect absorbers in Pd gratings, who both reported reflection ratios of <1000. 50,51 As above, it is interesting to note that the structures involving Ti exhibit unique behavior amongst the materials we investigated. The resonances in the Ti devices shift to shorter wavelengths after the hydrogenation reaction due to the increase in refractive index, in contrast to the red shifts demonstrated with the other two metals.…”
Section: Tunable Nanophotonics With Metal Hydridesmentioning
confidence: 81%
“…This offers significantly improved performance compared to Walter et al who presented reflection changes in Pd nanodiscs or Tittl et al who demonstrated perfect absorbers in Pd gratings, who both reported reflection ratios of <1000. 50,51 As above, it is interesting to note that the structures involving Ti exhibit unique behavior amongst the materials we investigated. The resonances in the Ti devices shift to shorter wavelengths after the hydrogenation reaction due to the increase in refractive index, in contrast to the red shifts demonstrated with the other two metals.…”
Section: Tunable Nanophotonics With Metal Hydridesmentioning
confidence: 81%
“…Metamaterial perfect absorbers (MPAs) possess exotic EM radiative properties, which may open up potential applications in the signature control of military targets to evade detection, such as in tanks, aircrafts, and ships by acting as radar absorbers, selective emitters, and infrared (IR) camouflage . To achieve perfect absorption at a specific wavelength, metal–dielectric–metal (MDM) structured metamaterials harness the inevitable loss that is present in all real‐life applications. In principle, perfect absorption is achieved in an MDM structure by: 1) obtaining zero reflection by matching the impedance; 2) obtaining zero transmission by using the metal ground, and 3) obtaining perfect absorption by maximizing the losses.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the self‐assembled spheres (or after a particular modification) can also be used as templates to produce various nanostructures in conjugation with different etching or deposition steps. This method, known as CL, has been well established in recent years, and is now recognized as a low‐cost, high‐throughput, scalable, and repeatable nanofabrication technique. In this work, a strategy based on CL has been developed to produce periodic nanohole arrays of a photoreconfigurable polymer deposited on a gold surface.…”
Section: Resultsmentioning
confidence: 99%